Taxonomic status, occurrence and lectotypification in the genus Ophiuros (Poaceae) in India - Gosavi, Kumar Vinod C.; Kambale, Sharad S.; Janarthanam, Malapati K. (Phytotaxa, 2019)
Present status and taxonomically valuable characters of Ophiuros (Poaceae) have been discussed. The distribution of O. exaltatus and O. megaphyllus is provided based on field survey and herbarium consultation in various herbaria in India. Lectotype for O. megaphyllus have been designated.